2016
DOI: 10.1016/j.surge.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of rapid maxillary expansion on the naso-maxillary facial soft tissue using 3D stereophotogrammetry

Abstract: Background: Rapid maxillary expansion (RME) is used to expand the narrow

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…In the present study, alar base width increased 1.98 mm in treated group compared with control, but the difference might not be clinically significant in the impact of the whole face, even though a large effect was detected between the groups for this variable. Other studies showed increase in nasal width after RME treatment in accordance with the present results …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, alar base width increased 1.98 mm in treated group compared with control, but the difference might not be clinically significant in the impact of the whole face, even though a large effect was detected between the groups for this variable. Other studies showed increase in nasal width after RME treatment in accordance with the present results …”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the direct measurements on the face are necessarily accompanied by a distortion of the soft tissue or by a difficult identification of the landmarks . Due to the inaccuracy of these methods to quantify soft tissue changes, the proposal of alternative techniques has continuously grown as 3D analysis through stereophotogrammetry or cone beam computed tomography (CBCT) …”
Section: Introductionmentioning
confidence: 99%
“…3 Nasal width increase was reported in studies using serial frontal photographs 6 and anthropometric measurements. 7 Three-dimensional (3-D) evaluation of widths of the nasal base, 8,9 mouth, 8 and columella 9 increased with flattening of the nose 9 and upper lip elongation and thinning. 10 3-D stereophotogrammetry is a method of acquiring images using one or more pairs of simultaneously taken photographs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the dental and skeletal effects of expansion using dental or skeletal anchorage are well documented, little information is available concerning the overlying soft tissue changes following these treatment modalities. The authors who have analyzed soft tissue changes associated with RME and SARME were more interested with naso-maxillary region ( 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ). They reported modifications in cheek, upper lip and nasal morphology which were explained majorly by the transversal enlargement of the maxilla, except for few studies ( 19 , 23 ) reporting that RME did not have significant clinical effects on the nose.…”
Section: Introductionmentioning
confidence: 99%
“…The authors who have analyzed soft tissue changes associated with RME and SARME were more interested with naso-maxillary region ( 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ). They reported modifications in cheek, upper lip and nasal morphology which were explained majorly by the transversal enlargement of the maxilla, except for few studies ( 19 , 23 ) reporting that RME did not have significant clinical effects on the nose. Furthermore, it has been pointed out that the immediate maxillary advancement with downward and backward mandibular rotation during maxillary expansion could have an effect on the patients’ soft tissue profiles ( 24 , 25 , 26 , 27 , 28 , 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%